Language myths and the history of English - Watts, Richard J. (Oxford Oxford University Press, 2011)
This book aims to deconstruct the myths that are traditionally reproduced as factual accounts of the historical development of English, and to reveal new myths that are currently being constructed.
Includes bibliographical references and index.
Keywords: English language -- History; English language -- Social aspects; Sociolinguistics; Discourse analysis